Social Capital Accumulation Shaping Consumer Loyalty: Alternative Consumer (Third Sector Social Economic Review, 2026)
This study examines the impact of social capital components on cooperative commitment and repurchase intention within alternative consumer cooperatives. Social capital is conceptualized through three dimensions: social interaction, consumer trust, and producer–consumer interaction. Survey data were collected from 450 consumers who shop at alternative consumer cooperatives. The data were analyzed using SPSS, employing correlation, regression, and demographic difference analyses.The findings indicate that social interaction significantly increases consumer trust, while consumer trust and particularly producer–consumer interaction are significant predictors of cooperative commitment. The direct effect of social interaction on commitment was not found to be significant. Moreover, cooperative commitment positively influences repurchase intention. Shared ethical value alignment also emerges as a strong predictor of repurchase intention.By integrating social capital theory with consumer behavior literature, this study demonstrates that consumer behavior in alternative cooperatives is shaped by relational and normative dynamics. The results highlight the strategic importance of trust-building mechanisms and producer–consumer interaction for the long-term sustainability of alternative consumer cooperatives.
Keywords: Alternative consumer cooperatives; social capital; consumer trust; cooperative commitment; repurchase intention